Mangrove Planting on Cemara Beach for Sustainable Development Goals (SDGs) - Agastya, Dewandha Mas; Raissilki, Muhammad Iqbal; Setiawan, Agustono; Budastra, Wayan Cintya Ganes; Rassy, Regania Pasca; Dewi, Evrianti Syntia; Sarjan, Achmad Fajar Narotama; Salsabila, Fera Fitri (Pascasarjana Universitas Mataram, 2024)
Sustainable Development Goals (SDGs) in protecting marine and coastal ecosystems and reducing the risk of natural disasters can be achieved through mangrove planting activities at Cemara Beach. Mangroves are useful in maintaining ecosystem balance, protecting the coastline from abrasion and absorbing carbon dioxide which can reduce the impact of climate change. Mangrove planting activities involve local communities in the planting and maintenance process, and contribute to improving community welfare and environmentally-based economic development. Mangrove planting activities use seedlings aged 3 to 6 months. Mangrove planting is in a location with a water depth of 10 to 50 cm. The size of the mangrove seedlings planted is 15 to 30 cm. The type of mangrove planted at Cemara Beach is Rhizophora. Mangrove planting activities support SDGs 13, 14, dan 15 tentang climate action, life below water, and life on land.